11 - ‘Arming the Rebels for Development’: Parental Involvement among Fishing Communities in Tanzania - Wabike, Paul (Africa Development, 2021)
The reality of life for children in the fishing villages of Tanzania’s inner lakes is: the father (or the head of the family who often happens to be a man) is fishing the whole night and sleeping during the day. The mother sleeps during the night and is either selling fish in one of the markets or is working on the land during the day. This circle often knows no weekends or public holidays and allows little room for contacts between parents/guardians and children, forcing children to morally and emotionally raise themselves or/and attach themselves to any other available authority. These children do not attend any formal schooling and are often are labelled watoro (absent from school) or ‘rebels’. While the formal education system demands that children of school-going age be at school, the fishing community’s social organisation and the labour market follows different patterns that do not really allow for optimal presence of parents to raise their children. This paper looks at the present state of families with school-age children in rural Tanzania and the problems they face in engaging fully in their children’s lives. Using the theories of Parental Involvement (PI) and Cultural Capital (CC), a survey carried out for this study found out that being present or absent from school for the children is not always a question of lack of time; it has often to do with what is considered important in the society on one hand and the demands exerted by the nature of income generating activities such as fishing, business and farming, on the other.